2011
DOI: 10.1590/s0103-64402011000500012
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of cognitive-behavioral therapy and amitriptyline in patients with chronic temporomandibular disorders: a pilot study

Abstract: The aim of this pilot study was to evaluate the effectiveness of cognitive-behavioral therapy (CBT) and use of amitriptyline, a tricyclic antidepressant, in patients with chronic temporomandibular disorders (TMD). Forty-seven women (mean age = 35.4 years old) with chronic TMD were enrolled in the study and divided into 4 groups: amitriptyline; amitriptyline and CBT; placebo and CBT; and placebo only (control). Patients were managed for 7 consecutive weeks. Follow-up evaluations were done at the 1st, 7th and 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 19 publications
1
9
0
10
Order By: Relevance
“…O tratamento cognitivo comportamental tem eficácia comprovada na DTM 14 . No entanto, a maioria dos pacientes recebe apenas o tratamento dentário sem abarcar as demandas psicológicas muitas vezes presentes nesta disfunção.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…O tratamento cognitivo comportamental tem eficácia comprovada na DTM 14 . No entanto, a maioria dos pacientes recebe apenas o tratamento dentário sem abarcar as demandas psicológicas muitas vezes presentes nesta disfunção.…”
Section: Discussionunclassified
“…Resultados favoráveis também foram encontrados com a TCC associada ao tratamento convencional de DTM e associação à terapia com Amitriptilina 11,14,15,22 . Dentre os benefícios foi descrito auxilio tanto no tratamento da dor quanto no enfrentamento da dor na íntegra, demonstrandose a necessidade da inclusão do tratamento psicológico dentro da clínica de DTM 15,22 .…”
Section: Discussionunclassified
“…Psychological treatment is often integrated to multi-and interdisciplinary programs which gather the action of different health professionals, among them: physiotherapists, occupational therapists, physicians and others 5 . With regard to intervention programs objectives, it was observed that, among selected studies, two have evaluated the efficacy of sequentially applied GCBT and physiotherapy 20,21 ; one has evaluated the effect of a single intervention by physician, occupational therapist, physiotherapist, psychologist and social worker, where some GCBT techniques were inserted 22 ; one has compared the effects of pharmacological treatment versus GCBT 23 ; and two have evaluated the effect of GCBT alone. Table 1 shows major data characterizing studies, especially with regard to evaluation, intervention and results.…”
Section: Contentsmentioning
confidence: 99%
“…Por isso,um aspecto a ser considerado na resposta ao tratamento é o efeito placebo, que é definido como mudanças psicológicas e fisiológicas positivas associadas com a administracao de substâncias inertes ou procedimentos (Calderon et al, 2011).…”
Section: Tratamentounclassified
“…O uso do placebo em estudos controlados é sugerido como a mais apropriada forma de comprovar ou contestar uma modalidade de tratamento, especialmente em casos de entidades multifatoriais, quando não há método universal disponível (Calderon et al, 2011).…”
Section: Efeito Placebounclassified